Correlation of Neuroendocrine Differentiation with Neuroendocrine Cell Hyperplasia and Vascular Endothelial Growth Factor in Colorectal Adenocarcinoma - Khesar Hussein Khalil; Bashar Al-Hassawi; Jasim Abdo (مجلة بغداد للعلوم)
Neuroendocrine differentiation has been mentioned in many cancers of non-neuroendocrinal organs, involving the gastrointestinal tract. In contrast, the correlation of focally diffused neuroendocrine differentiation in colorectal adenocarcinoma with neuroendocrine cell hyperplasia has not been somewhat reported. The objective of this research is to study the relationship between neuroendocrine cell hyperplasia and neuroendocrine differentiation in colorectal adenocarcinoma and to find the correlation of neuroendocrine differentiation and VEGF expression with clinicopathological parameters of colorectal adenocarcinoma. Methods employed in the current study were including eighty-one patients with colorectal cancer. Formalin fixed paraffin embedded blocks were sectioned and stained with immunohistochemical markers; Chromogranin A and VEGF; and processed automatically according to protocols supplied by the antibody manufacturer. Results show that neuroendocrine cell hyperplasia in the mucosa nearby tumor comprised (42%) and it was associated with neuroendocrine differentiation. Neuroendocrine differentiation and vascular endothelial growth factor were positive in 48.1% and 63% respectively. Neuroendocrine differentiation did not show a relation with clinicopathological parameters with the exception of tumor that metastasizes to other tissues and organs. The association of VEGF with the same factors had significant impact with tumor stage, degree of local invasion and lymph node metastasis. Other histological changes revealed that only desmoplastic reaction had significant difference in relation to neuroendocrine differentiation. This study reached the conclusion that neuroendocrine cell hyperplasia is positively correlated with neuroendocrine differentiation and it has strong linkage in pathogenesis of colorectal adenocarcinoma. Neuroendocrine differentiation and VEGF expression are greatly correlated with progression and invasion of tumor to other tissues and organs, and this can be represented as an important parameter for poor prognosis of colorectal adenocarcinoma.